2010
DOI: 10.1002/asi.21440
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid citation-word representations in science mapping: Portolan charts of research fields?

Abstract: The mapping of scientific fields, based on principles established in the seventies, has recently shown a remarkable development and applications are now booming with progress in computing efficiency. We examine here the convergence of two thematic mapping approaches, citation-based and word-based, which rely on quite different sociological backgrounds. A corpus in the nanoscience field was broken down into research themes, using the same clustering technique on the 2 networks separately. The tool for compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…The combination of both has proven to be highly effective in representing the conceptual content of articles (13,14). We collected 47,667 different words that were corrected unifying grammatical variants and using only one key word for singulars and plurals, adjectives, and nouns, acronyms, and developed names of the same concept, among others.…”
Section: Productivity Citations Collaboration Patterns and Key Wormentioning
confidence: 99%
“…The combination of both has proven to be highly effective in representing the conceptual content of articles (13,14). We collected 47,667 different words that were corrected unifying grammatical variants and using only one key word for singulars and plurals, adjectives, and nouns, acronyms, and developed names of the same concept, among others.…”
Section: Productivity Citations Collaboration Patterns and Key Wormentioning
confidence: 99%
“…They found that communities and topics are interwoven and co-evolving. Hybrid approaches can integrate different types of scholarly networks, for example, citation-based and word-based networks (Janssens et al, 2008;Liu et al, 2010;Zitt et al, 2011) and co-occurrence networks (Boyack & Klavans, 2010), but these studies were largely focused on providing more precise clustering results but did not address the interactive nature of research topics and communities.…”
Section: Overlaying Communities With Topicsmentioning
confidence: 99%
“…Their hybrid approach can be employed as a good reference for journal categorization. Zitt, Lelu, and Bassecoulard (2011) examined the convergence of two thematic mapping approaches: citation-based and word-based. They found the two approaches yield quite different outcomes and cannot substitute each other.…”
Section: Identifying Topicsmentioning
confidence: 99%
“…1 The framework of our search strategy for science Scientometrics combinations and classifications underlying search strategies are necessary for targeted scientific and technological domains (Thomas et al 2011). Citation-based analysis, as a means to identify a corpus of literature embodied in electronic records, is effective in identifying communities of researchers and research streams (Zitt et al 2011). At the same time, core journal search whose scope falls into the domain field should also be taken into consideration to help identify on-target research publications for a target emerging science or technology domain.…”
Section: Introductionmentioning
confidence: 99%